2023
DOI: 10.1002/ente.202201200
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks‐Based Cathode Materials for Energy Storage Applications: A Review

Abstract: Metal-organic framework (MOF) are a kind of highly organized porous crystalline material that has attracted significant interest in several applications, including chemical sensors, organic-, photo-, and electrocatalysis, and energy and environmental applications. [1][2][3][4][5][6] Yaghi et al. are pioneers in the development of MOF-based porous materials using organic linkers and metal-oxide clusters as anchors to create open frameworks. [7] MOFs are readily manufactured by reacting metal ions or clusters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 150 publications
0
9
0
Order By: Relevance
“…At present, materials with more research on the cathode of ZIBs mainly include manganese-based, vanadium-based, Prussian blue, and some conductive organic materials. [73][74][75][76] Among them, manganese-based and vanadium-based oxides are the most widely studied cathode materials. Manganese-based oxides have high working voltage and high theoretical capacity for zinc storage.…”
Section: Cathodesmentioning
confidence: 99%
“…At present, materials with more research on the cathode of ZIBs mainly include manganese-based, vanadium-based, Prussian blue, and some conductive organic materials. [73][74][75][76] Among them, manganese-based and vanadium-based oxides are the most widely studied cathode materials. Manganese-based oxides have high working voltage and high theoretical capacity for zinc storage.…”
Section: Cathodesmentioning
confidence: 99%
“…[50,52,54,190] Furthermore, MOF materials possess characteristics such as large surface area, tunable porosity, flexible topology, flexible dimension, and chemical functionality, making them of wide interest in the field of energy harvesting and storage. [2,[191][192][193][194] Multiple works have reported the application of MOF in highperformance TENG. [53,56,[195][196][197][198] For instance, Khandelwal et al first reported the use of zeolitic imidazole framework (ZIF) MOF-based TENG for self-powering systems and sensor applications (Figure 8a).…”
Section: Applications In the Energy Harvesting And Storagementioning
confidence: 99%
“…In the past few decades, several studies have extensively investigated the application of ESTs in renewable energy grid connection, [9][10][11] distributed generation and microgrid, [12][13][14] electric vehicle energy storage applications, [15][16][17] and power transmission. [18][19][20] The article in ref.…”
Section: Introductionmentioning
confidence: 99%